Asymmetrical ignition of radio frequency discharge in atmospheric pressure cascade glow discharges. (1st March 2023) - Zhang, Yarong; Fang, Junlin; Xu, Shaofeng; Guo, Ying; Shi, Jianjun
Abstract: A two-dimensional self-consistent fluid model was developed to investigate the ignition of radio frequency (RF) discharge in an atmospheric helium cascade glow discharge. In particular, the model considers the case where a pulsed discharge is excited ahead of the RF discharge by applying pulsed DC voltage and RF voltage to two parallel plate electrodes separately. The spatio-temporal distribution of electron, ion, electric field, and mean electron energy demonstrate that the electron and ion localize in the vicinity of RF electrode with the extinguishment of pulsed discharge, whereas a sheath region formed above the pulsed electrode due to the space charge. It explains the experimental findings of asymmetric ignition of RF discharge in the interelectrode gap. With the migration of ion towards the pulsed electrode, the RF discharge achieves the stable operation. Furthermore, the migration time of ion from the RF electrode to pulsed electrode is estimated to be 3.0 μ s, which is consistent with the calculated migration time of ions across the discharge gap.